Perceived Barriers and Benefits of Exercise Among Women Survivors of Sexual Violence by Physical Activity Level and Posttraumatic Stress Disorder Status - Pebole, Michelle M. (Violence against women, 2024)
An online, cross-sectional survey of women survivors of sexual violence (SV; N = 355) gathered information on perceived barriers and benefits of exercise, along with exercise level and posttraumatic stress disorder (PTSD) symptoms. This study reports exercise perceptions and provides comparisons by exercise level and PTSD status. Differences by exercise level were found in life enhancement, physical performance, psychological outlook, and social interaction (ps < 0.05; rs = −0.04–0.25). Differences were found by PTSD status in physical performance, social interaction, and preventative health and exercise milieu, time expenditure, and family discouragement (ps < 0.05; rs = −0.39–0.21). Findings provide new information relevant for promoting exercise among women survivors of SV.